Blood–Brain Barrier, Cell Junctions, and Tumor Microenvironment in Brain Metastases, the Biological Prospects and Dilemma in Therapies - Guan, Zhiyuan; Lan, Hongyu; Cai, Xin; Zhang, Yichi; Liang, Annan; Li, Jin (Frontiers in Cell and Developmental Biology, 2021)
Brain metastasis is the most commonly seen brain malignancy, frequently originating from lung cancer, breast cancer, and melanoma. The brain tumor has its unique cell types, anatomical structures, metabolic constraints, and immune environment, which is called tumor microenvironment. It has been discovered that the tumor microenvironment can regulate the progression, metastasis, and response to the treatment of primary tumors through the particular cellular and non-cellular components. Brain metastasis tumor cells that penetrate the brain-blood barrier and blood-cerebrospinal fluid barrier to alter the function of cell junctions would lead to the different tumor microenvironment. Emerging evidence implies that these tumor micro environment components would be involved in mechanisms of immune activation, tumor hypoxia and anti-angiogenesis, etc. Researchers have applied various therapeutic strategies, such as the combination of brain radiotherapy, immune checkpoint inhibitors, and monoclonal antibodies. Unfortunately, they hardly access effective treatment. Meanwhile, most clinical trials of target therapy patients with brain metastasis are always excluded. In this review, we summarized the clinical treatment of brain metastasis in recent years, as well as the differences between the composition of tumor microenvironment in the primary tumor and brain metastasis. We also analyzed the feasibility and superiority of tumor microenvironment-targeted-therapies, which may help to improve the strategy of brain metastasis treatment.